Cationic polymerization of epoxides using novel xanthenyl phosphonium salts as thermo-latent initiator - Gupta, Mukesh Kumar; Singh, Raj Pal (Polymer Bulletin, 2008)
The present article describes the effect of steric and electronic factors on the efficiency of initiators based on novel xanthenyl phosphonium salts for cationic polymerization of epoxide monomers. 2-substituted (I(H), I(Cl), I(Me), and I(OMe)) xanthenyl phosphonium hexafluoroantimonate were synthesized and characterized by NMR ((1)H, (13)C and (31)P) and IR spectroscopy. The order of initiator activity in polymerization of glycidyl phenyl ether (GPE), was found as I(H)> I(Cl)> I(Me)> I(OMe). To understand the effect of steric factor, the polymerization of cyclohexene oxide (CHO) was performed and the order of activity was found as I(Cl)> I(H)> I(Me) > I(OMe). All the initiators were found to be latent at ambient temperature and initiates polymerization on thermal initiation. The order of initiator activity was influenced by electronic and steric factors in the system. The thermal stability of these salts was measured by Thermo gravimetric analysis (TGA). The solubility of the initiators in various organic solvents and epoxy monomers is also discussed.